FROM WOUNDS TO STRENGTH: THE ROLE OF GUIDANCE AND COUNSELING IN ROMANTIC CONFLICT - Faerosa Faerosa; Lisa Auliya Insani (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
This literature review discusses the role of guidance and counseling in helping adolescents cope with romantic conflicts, which often negatively impact their mental health. The study reviews 4,019 counseling sessions and finds that cognitive behavioral therapy (CBT) is effective in changing negative thought patterns and improving emotion management. Additionally, online counseling provides easier access for adolescents to obtain support. The review emphasizes the importance of effective communication skills, emotion regulation, and realistic expectations in building healthy relationships, and highlights the need for comprehensive guidance and counseling programs to help adolescents face challenges in their romantic relationships positively.